The architect of victory the military career of Lieutenant-General Sir Frank Horton Berryman - Dean, Peter J. 1974- (Australian Army history series, 2011)
Lieutenant General Sir Frank Berryman is one of the most important, yet relatively unknown officers in the history of the Australian Army. Despite his reputedly caustic personality and noted conflicts with some senior officers, Berryman was crucial to Australia's success during the Second World War. But did the man known as 'Berry the Bastard' deserve his reputation? Bold, calculating and talented, Berryman was at the forefront of operations that led to the defeat of the Japanese, and his operational planning secured Australia's victories at Bardia, Tobruk and in New Guinea during the Pacific War. With access to rare private papers, Peter Dean charts Berryman's special relationships with senior US and Australian officers such as MacArthur, Chamberlin, Blamey, Lavarack and Morshead, and explains why the man poised to become the next Chief of General Staff would never fulfil his ambition